Pengetahuan, Sikap dengan Partisipasi Pedagang Dalam Pengelolaan Sampah Pasar - Muhammad Sufriannor; Hardiono Hardiono; Juanda A. Zuraini (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: Knowledge, Attitude with Merchants Participation In The Management of Market Waste. In Banjarbaru city waste volume transported by TPS officers per day about 90 tons / day to TPA. One of the source of waste is the market which is a big problem because most of the market waste is wet garbage. So these waste piles become flies nest, rats, insects.Waste management is also influenced by the participation of merchants that were still lacking awareness to play an active role in the implementation. The purpose of this study is to determine the relations of knowledge, attitude with the participation of merchants in waste management in the Bauntung market Banjarbaru. The type of this research is analytical survey research with Cross Sectional approach. The population in this study is all merchants in the Bauntung market Banjarbaru. The sample is 85 respondents, obtained by proportional sampling method. The research variables consist of independent variables, namely knowledge and attitude while the dependent variable is the participation of merchants in waste management. Data analysis used is univariat and bivariate (using Chi Square with α = 0,05). The result of the research stated that there is no correlation between knowledge level and participation (p-value 0,747> 0,05). There is a correlation between attitudes with participation (p-value 0.001